2017
DOI: 10.1111/cei.12968
|View full text |Cite
|
Sign up to set email alerts
|

In vivoactivation of invariant natural killer T cells induces systemic and local alterations in T-cell subsets prior to preterm birth

Abstract: Preterm birth, the leading cause of neonatal morbidity and mortality worldwide, is frequently preceded by spontaneous preterm labour, a syndrome of multiple aetiologies. Pathological inflammation is causally linked to spontaneous preterm labour. Indeed, direct activation of invariant natural killer T (iNKT) cells via α-galactosylceramide induces preterm labour/birth largely by initiating systemic and local (i.e. decidua and myometrium) innate immune responses. Herein, we investigated whether iNKT-cell activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 82 publications
0
22
1
Order By: Relevance
“…In contrast with our findings, studies in mouse models of preterm birth have demonstrated changes in frequency and proinflammatory and prolabor function for T cells, iNKT cells, and Tregs in the chorio-decidua, implicating these cells in the pathogenesis of inflammation-mediated preterm birth (59)(60)(61)(62). Besides species differences, different route (systemic vs. IA route in our study) of administration of proinflammatory agents might explain these different findings.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast with our findings, studies in mouse models of preterm birth have demonstrated changes in frequency and proinflammatory and prolabor function for T cells, iNKT cells, and Tregs in the chorio-decidua, implicating these cells in the pathogenesis of inflammation-mediated preterm birth (59)(60)(61)(62). Besides species differences, different route (systemic vs. IA route in our study) of administration of proinflammatory agents might explain these different findings.…”
Section: Discussioncontrasting
confidence: 99%
“…During early and mid‐pregnancy, macrophages displaying an alternative or M2‐like phenotype are the dominant decidual subset, indicating that such cells may play an important role in maternal‐fetal tolerance throughout pregnancy . At the end of gestation, during the physiological process of labor, decidual macrophages acquire an M1‐like phenotype, a phenomenon that also occurs during the pathological process of preterm labor and coincides with the infiltration of other inflammatory cells at the maternal‐fetal interface . Disruption of the decidual macrophage population has been linked to placental dysfunction and disease .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, maternal CD8+ regulatory T cells have been implicated in the systemic and local (i.e. the maternal-fetal interface) immune mechanisms that lead to spontaneous preterm labor [70, 71]. CD8+ regulatory T cells are induced extrathymically through antigen presentation in the neonatal period in mice [72]; however, their role in humans is unknown.…”
Section: Discussionmentioning
confidence: 99%